Implementasi Pendidikan Inklusi dalam Pendidikan Islam - Kharisul Wathoni (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
Everybody has right to be educated, not excluded the diffable people. Unfortunately, they are large in number but small in access. The diffable get limited access including access of education especially in Islamic education institution. This article attempts to discuss some alternatives of model of education which accommodates the need of the diffable, namely, full inclusion and partial inclusion.